2020
DOI: 10.1101/cshperspect.a039339
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Central Amygdala in Alcohol Dependence

Abstract: Alcohol dependence is a chronically relapsing disorder characterized by compulsive drugseeking and drug-taking, loss of control in limiting intake, and the emergence of a withdrawal syndrome in the absence of the drug. Accumulating evidence suggests an important role for synaptic transmission in the central nucleus of the amygdala (CeA) in mediating alcoholrelated behaviors and neuroadaptive mechanisms associated with alcohol dependence. Acute alcohol facilitates γ-aminobutyric acid (GABA)ergic transmission in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
89
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(92 citation statements)
references
References 234 publications
(271 reference statements)
1
89
0
2
Order By: Relevance
“…The CeA serves as an integrative hub mediating key aspects of negative emotional states associated with alcohol dependence, including anxiety-like behaviors (Gilpin et al, 2015). The CeA is a mainly GABAergic nucleus, particularly sensitive to both acute and chronic ethanol (Roberto et al, 2003(Roberto et al, , 2004(Roberto et al, , 2020. Thus, elevated CeA GABA transmission is a characteristic of alcohol dependence across species, including humans (Roberto et al, 2004;Augier et al, 2018;Jimenez et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The CeA serves as an integrative hub mediating key aspects of negative emotional states associated with alcohol dependence, including anxiety-like behaviors (Gilpin et al, 2015). The CeA is a mainly GABAergic nucleus, particularly sensitive to both acute and chronic ethanol (Roberto et al, 2003(Roberto et al, , 2004(Roberto et al, , 2020. Thus, elevated CeA GABA transmission is a characteristic of alcohol dependence across species, including humans (Roberto et al, 2004;Augier et al, 2018;Jimenez et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…This is of interest because cSNC effects have shared neurochemical and neurobiological underpinnings with addiction (for a review, see Ortega et al, 2017); for example, recent research has shown that inactivation of the central amygdala (CeA) prevents a cSNC effect following a sucrose downshift task (Guarino et al, 2020). These findings suggest that the CeA, a brain region also implicated in the development of AUD (for a review, see Roberto et al, 2020), is crucial for cSNC. Recent work has also found that rats exposed to binge levels of EtOH during adolescence show greater cSNC (lower sucrose consumption) following a downshift protocol than control (Lerma-Cabrera et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, alterations in the expression of genes encoding some GABA A and GABA B receptor subunits, as well as GABA transporters, have been shown to influence the predisposition to high alcohol consumption and vulnerability to AUD in humans, as well as AUD-like behaviour in rodents 11,12 . The central nucleus of the amygdala (CeA) is a key neural locus in which the GABAergic system mediates neuroadaptations involved in alcohol drinking behaviours 13,14 . Both acute and chronic alcohol exposure increase GABAergic transmission in CeA and alcoholdependent rats show increased baseline GABA levels in the CeA compared to alcohol-naïve rats 13,14 .…”
Section: Introductionmentioning
confidence: 99%
“…The central nucleus of the amygdala (CeA) is a key neural locus in which the GABAergic system mediates neuroadaptations involved in alcohol drinking behaviours 13,14 . Both acute and chronic alcohol exposure increase GABAergic transmission in CeA and alcoholdependent rats show increased baseline GABA levels in the CeA compared to alcohol-naïve rats 13,14 . Infusion of a GABA A receptor antagonist into the CeA reduces alcohol selfadministration in non-dependent rats 15 , whereas microinjection of a GABA A receptor agonist reduces self-administration in alcohol-dependent but not in non-dependent rats 14,16 , indicating that the development of alcohol dependence is associated with adaptations in the GABAergic system within the CeA.…”
Section: Introductionmentioning
confidence: 99%